Possibility of screening for mild cognitive impairment via an eye tracking-based cognitive scale - Naoki Kodama; Sou Takahashi; Masazumi Tsuji; Yuji Kawase; Satoshi Naruse; Katsuya Urakami (Frontiers in Aging, 2025)
IntroductionThe Montreal Cognitive Assessment (MoCA) is widely used as a screening test for mild cognitive impairment (MCI). However, the MoCA takes approximately 15 min to administer and evaluate by skilled examiners, such as medical professionals. This study assessed whether an eye tracking-based cognitive scale using virtual reality (VR) was accurate and efficient to screen for MCI.MethodsThis study included 143 patients. The Virtual Reality-Based Cognitive Function Examination (VR-E) was used with all participants to evaluate their memory, judgment, spatial cognition, calculation, and language function.ResultsSignificant differences were observed in all cognitive domains of memory, judgment, spatial cognition, calculation, and language function between the Alzheimer’s disease (AD), MCI, and older healthy control (HC) groups. The area under the curve value of the VR-E score for the HC and MCI groups was 0.857, and that for the AD and MCI groups was 0.870. The correlation coefficient between the MMSE and VR-E scores was 0.566 (p < 0.001), and that between the Japanese version of the MoCA (MoCA-J) and VR-E scores was 0.648 (p < 0.001), which indicated a moderate correlation in both comparisons.ConclusionThe VR-E had the same diagnostic performance results as the MoCA-J, thus the VR-E has potential for use in screening patients for MCI.